A Comparative Study on the Influence of Transliteration and Free Translation of Brand Names in Brand Infiltration on Consumer Willingness - Wang and Xinyue Hu, Peipei (British Journal of Marketing Studies, 2018)
In the infiltration process of brand localization and internationalization, the translation of its name has important academic research value and practical significance. On the transliteration and free translation of brand names, the academic research is not sufficient and not well targeted. In this paper, a controlled experiment which is a combination of questionnaires and psychological experiments was conducted. The one-way stimulation of the brand name transliteration or free translation of the subjects directly and indirectly was measured to determine the familiarity and willingness of consumers in China to foreign brands. The results show that in the initial stage of brand infiltration, the positive stimulating effect of transliteration on consumer willingness is more significant, but with the comprehensive and deep knowledge of consumers' brand knowledge, the brand name of free translation is more durable enough to stimulate consumers' willingness to consume.